1995
DOI: 10.1002/pssb.2221920114
|View full text |Cite
|
Sign up to set email alerts
|

Polarized XANES Studies of Cu L3 Edges of Bi‐2212 Superconducting Single Crystals Using Total and Fluorescence Yield Techniques

Abstract: XANES with polarized synchrotron light is now established to be one of the important techniques for the study of the electronic structure of high-T, superconductors in order to find out the symmetry of holes and their implication to the theoretical models proposed to explain superconductivity in these cuprates. The XANES spectra are measured by two methods in the soft X-ray region, namely, total yield (TY) and fluorescence yield (FY) methods, which give different results with respect to out-of-plane Cu 3d(z2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Later reports using the bulk-sensitive 0953-8984/96/142467+11$19.50 c 1996 IOP Publishing Ltd 2467 fluorescence yield (FY) mode [12] showed an almost insignificant intensity for the out-ofplane Cu 3d z 2 states. A recent report by Venkatesh et al [21] lists the probable reasons for the observed discrepancies in the TY and FY data. Still no satisfactory explanation has been given so far regarding the various contradictory observations reported.…”
Section: Introductionmentioning
confidence: 99%
“…Later reports using the bulk-sensitive 0953-8984/96/142467+11$19.50 c 1996 IOP Publishing Ltd 2467 fluorescence yield (FY) mode [12] showed an almost insignificant intensity for the out-ofplane Cu 3d z 2 states. A recent report by Venkatesh et al [21] lists the probable reasons for the observed discrepancies in the TY and FY data. Still no satisfactory explanation has been given so far regarding the various contradictory observations reported.…”
Section: Introductionmentioning
confidence: 99%
“…This served to show that the difference in the spectra from the two techniques perhaps mainly arises from the condition of the surface. An earlier report by S. Venkatesh et al(1995) wherein they report a larger intensity the for the Cu L III edge in the FY mode compared to that from the TY mode from a crystal not cleaved in situ also tends to confirm this. Pellegrin et al(1993) have indicated how an alignment error of up to +5% may also contribute to the discrepancies in the measured intensities.…”
Section: Methodsmentioning
confidence: 55%